Exploring the Dynamics of Social Media Addiction Among Indonesian Users - Izzah Illiyyina; Aula Regita Dewi Fitriana; Nabila Septia Rosa; Ananda Helena Nurul Izzah; Aji Ramadhan Choirur Rofiansyah (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This study, employs a literature review method to examine the psychological, social, and regulatory dimensions of social media addiction in Indonesia. Findings reveal that excessive social media use negatively affects mental health, leading to anxiety, sadness, low self-esteem, and vulnerability to cyberbullying. To address these issues, the study highlights Cognitive Behavioral Therapy (CBT) as an effective intervention to reshape maladaptive thought patterns. Additionally, enhancing media literacy, strengthening cybersecurity awareness, and implementing public education campaigns such as “Socially Smart Awareness” are crucial in promoting healthier digital behavior. The research also emphasizes the need for regulatory measures that ensure user protection while maintaining justice and digital freedom. Overall, integrated psychological, educational, and policy-based approaches are essential to mitigate the adverse effects of social media addiction among Indonesian users.